2020
DOI: 10.1002/batt.202000125
|View full text |Cite
|
Sign up to set email alerts
|

Fast Li+ Transport of Li−Zn Alloy Protective Layer Enabling Excellent Electrochemical Performance of Li Metal Anode

Abstract: Li alloy film has been developed as an advanced artificial protection layer on Li metal anode, attributed to its tight contact with Li metal and unique transportation capability of mixed ion/electron. Li+ diffusion coefficient of the alloy interphase layer is crucial for Li dendrite growth and rate performance. Here, Zn thin film is sputtered on the surface of Li foil, and Li−Zn alloy buffer layer is spontaneously formed via an alloying reaction. In the process of electrochemical cycling, while Li+ ions are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Figure 1(c) shows the photographs for the pristine Li foil (left) and a LiZn‐protected Li foil (right). The bare lithium presents a metallic grey color while after Zn deposition via sputtering, a homogeneous gold color was observed, which is typical of a LiZn alloy [57] . Depending on the deposition conditions, a slight change in the intensity of gold color is observed that suggests a difference of texture for the LiZn layers.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Figure 1(c) shows the photographs for the pristine Li foil (left) and a LiZn‐protected Li foil (right). The bare lithium presents a metallic grey color while after Zn deposition via sputtering, a homogeneous gold color was observed, which is typical of a LiZn alloy [57] . Depending on the deposition conditions, a slight change in the intensity of gold color is observed that suggests a difference of texture for the LiZn layers.…”
Section: Resultsmentioning
confidence: 96%
“…In this work, the modification of lithium foils with a nanometric layer of Zn deposited by sputtering is reported. Zn has been chosen for its relatively low price and because the LiZn alloy has a high Li + ion diffusion coefficient [57] . The presence of the LiZn alloy was confirmed by XRD analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li-rich alloy SEI layers (featuring compositions of thermodynamically stable Li-alloys and Li) formed by artificial alloying reactions have been adopted on the Li metal surface. 12,13 To date, several alloy SEI layers have been reported, including LiIn, 14 LiZn, 15,16 LiAl, 17 LiCu, 18 and LiGa groups. 19 The experimental results show that the alloy SEI layers effectively reduce the Li nucleation overpotential and lead to dense non-dendrite Li deposition, excellent coulombic efficiency and ultra-long cycling stability of the cell.…”
Section: Introductionmentioning
confidence: 99%